Optical deposition of nano carbon materials for fiber-based saturable absorbers - Yang, Y. (2013)
We demonstrated the manipulation of carbon nanotubes (CNTs) and graphene on optical fiber ends for saturable absorbers (SAs) by optical deposition method. The nonlinear absorption of the prepared CNT-based SA is characterized and 0.9%-modulation depth is obtained. Furthermore, graphene can be deposited on fiber ends by using such controllable process. It is found that the desired optical power for triggering the CNTs to deposit towards the fiber ends is different from that of graphene. Potential applications of these carbon-based SAs are expected in mode-locked fiber lasers as well as Q-switched fiber lasers.